The effect of ergonomics education on musculoskeletal system, posture and ergonomic risk in university students. - Atalı, Gamze; Terzioğlu, Füsun (Work, 2026)
Background: Maintaining the correct posture is very important for students who spend most of the day at desks and tables. Objective: This study aimed to determine the effect of ergonomics training given to university students on their musculoskeletal system, postural habits, and awareness, and ergonomic risk score evaluated by the REBA (rapid entire body assessment) method. Method: A total of 130 university students participated in the study. The students were divided into two homogenized groups: intervention (65) and control (65). Only the intervention group received ergonomics training. All students were administered a semi-structured sociodemographic questionnaire, Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), and Postural Habits and Awareness Scale (PHAS) at the beginning of the study. The Rapid Whole Body Assessment (REBA) was used to assess ergonomic risk. Ergonomics training was given to the intervention group. In the evaluation of static endurance of the core muscles, the trunk flexor endurance test, the trunk extensor endurance test, and the time spent in the right-left lateral bridge test positions were calculated. The evaluations were repeated immediately after the training and 1 month after. Results: Following the training, no statistically significant differences were found between the CMDQ, PHAS, and core muscle endurance measurement groups. Additionally, ergonomics training was effective in reducing regional musculoskeletal complaints, decreasing ergonomic risk scores, and enhancing positional awareness. Conclusion: Ergonomics training should be utilized to gain correct posture habits and reduce musculoskeletal disorders.